Systematic Analysis of the Influence of Green Product Innovation on Sustainable Competitive Advantage in the Food Industry Sector - Prakoso, Sugih; Nugroho, Arissetyanto; Zulkifli (GoAcademica Research & Publishing, 2025)
This study aims to analyze the relationship between Green Product Innovation (GPI) and sustainable competitive advantage (SCA) in the context of MSMEs in the food sector in West Java. The approach used is the Systematic Literature Review (SLR) of 30 selected scientific articles from various international databases. The results of the analysis show that the main indicators of GPI include environmentally friendly product design, use of sustainable raw materials, green processing technology, and ecological packaging. The dominant dimensions of SCA include cost advantage, product differentiation, customer loyalty, sustainable innovation, and corporate image (green image). Most of the literature supports a positive relationship between GPI and SCA through the mechanisms of operational efficiency, increased brand value, and market attractiveness. There is a theoretical gap due to the lack of integration between GPI and classical strategy frameworks such as Resource-Based View (RBV) and Porter's Generic Strategies. This study provides practical contributions to the food industry through recommendations for systematic adoption of GPI, as well as theoretical contributions in strengthening the resource-based sustainability model. Further research is recommended to use quantitative and longitudinal approaches to deepen the understanding of the causal relationship between these key variables.